KESEHATAN TANAMAN KAYU PUTIH (Melaleuca leucadendra Linn) DI LAHAN REHABILITASI DAERAH ALIRAN SUNGAI (DAS) GUNUNG BATU DESA TEBING SIRING PELAIHARI KABUPATEN TANAH LAUT - Siti Raudatul Jannah; Gusti Muhammad Hatta; Basir Basir (Jurnal Sylva Scienteae, 2022)
Watershed (DAS) which is included in the category that must be restored is the Gunung Batu watershed in Tebing Siring Pelaihari Village. High land clearing for both the mining sector and oil palm plantations makes the watershed area in South Kalimantan very vulnerable to flooding so that it clearly has a major impact on increasing flood vulnerability, coupled with the number of land fires during the dry season so that the rainwater infiltration process is no longer running properly (Aulina et al. 2017). Watershed Rehabilitation Land in Gunung Batu Village was restored by replanting various types of forestry plants, one of which is eucalyptus (Melaleuca leucadendra). Eucalyptus was chosen as a revegetation plant because it is able to live in dry soil and does not have specific growing conditions. In order to know the state and condition of eucalyptus plants, data is needed as raw material for analysis. There is no record or data on the health of eucalyptus oil for the rehabilitation of the Gunung Batu watershed, so the authors are interested in conducting research on the health of the eucalyptus oil plant on the land. Based on the results of the study, the percentage of live eucalyptus plants in the rehabilitation area of the Gunung Batu watershed was 97.73% with an average height of 3.15 m and a diameter of 5.84 cm, the most damage was in the leaves. However, in general, eucalyptus plants in the Gunung Batu watershed, Tebing Siring Pelaihari Village, were healthy with an INK of 1.00.Daerah Aliran Sungai (DAS) yang termasuk kategori harus dipulihkan adalah DAS Gunung Batu Desa Tebing Siring Pelaihari. Pembukaan lahan yang tinggi baik untuk sektor pertambangan maupun perkebunan kelapa sawit membuat wilayah DAS di Kalimanatan Selatan sangat rentan banjir sehingga sangat jelas berdampak besar terhadap meningkatnya kerawanan banjir, ditambah dengan banyaknya kebakaran lahan sepanjang musim kemarau sehingga proses infiltrasi air hujan tidak lagi berjalan secara baik (Aulina et al. 2017). Lahan Rehabilitasi DAS Desa Gunung Batu dipulihkan dengan cara menanam kembali berbagai jenis tanaman kehutanan, satu diantaranya adalah jenis kayu putih (Melaleuca leucadendra). Tanaman kayu putih dipilih sebagai tanaman revegetasi karena mampu hidup di tanah yang kering serta tidak memiliki syarat tumbuh yang spesifik. Agar dapat mengetahui keadaan dan kondisi tanaman kayu putih maka diperlukan data sebagai bahan mentah analisis.  Pencatatan atau data kesehatan tanaman minyak kayu putih untuk lahan rehabilitasi DAS Gunung Batu sampai saat ini belum ada, sehingga penulis tertarik untuk melakukan penelitian mengenai kesehatan tanaman minyak kayu putih dilahan tersebut. Berdasarkan hasil penelitian persentase hidup tanaman kayu putih pada lahan rehabilitasi DAS Gunung Batu 97.73% dengan rerata tinggi 3,15 m dan diameter 5,84 cm, kerusakan paling banyak di bagian daun.  Namun secara umum tanaman kayu putih di DAS Gunung Batu Desa Tebing Siring Pelaihari adalah sehat dengan INK 1,00